(untitled) (Journal of the College of Education for Women, 2019)
The research aims to identify the relationship between dietary choices for kindergarten children and monthly income of the family and the impact of these choices on child growth study has shown a relationship between dietary choices that are chosen by the family and the monthly income. The greater the monthly income increased spending on food and therefore its impact on the health and development of the child and the less monthly income less spending on food purchases, leading to the emergence of diseases such as malnutrition, disease. Limited research on (90) children aged from (4-6) years in the center of Baghdad on both sides (Karkh and Rusafa) to Riyadh government and private Prominent search results and a statistically significant differences between the dietary choices for kindergarten children and monthly income of the family will be highlighted by the recommendations and proposals : (1) the need for integrated attention to the diet of children (quantity and quality) and in a scientific manner. (2) planning before buying food to suit the family’s monthly income. (3) conduct a study on the relationship dietary choices social situation of the family. (4) to conduct a study on the relationship of food choices for children sized family.